Forest Fire and Environmental Damage: The Indonesian Legal Policy and Law Enforcement - Adi Wijayanto; Hatta Acarya Wiraraja; Siti Aminah Idris (Unnes Law Journal, 2022)
Law enforcement regarding the environment is in fact a responsibility that should be fulfilled by the state. In this case, the state is the main actor in prevention, as well as a protector from any efforts to destroy nature and the environment. It can be understood that to maintain the crucial elements in the existence of a state, as agreed in the Montevideo Convention, among others, permanent residents, definite territory, government, the ability to enter into relations with the state. other. So with this it can be understood that environmental damage due to forest fires, is a form of threat also in the area element, because by burning ecosystems, it will result in an imbalance of life in an area, it can also be interpreted if the impacts arising from forest fires spread to enter the area. on the territory of neighboring countries, it will lead to unfavorable relations with other countries.